2017
DOI: 10.1186/s12889-017-4593-0
|View full text |Cite|
|
Sign up to set email alerts
|

Accuracy and determinants of perceived HIV risk among young women in South Africa

Abstract: BackgroundHIV risk perceptions are a key determinant of HIV testing. The success of efforts to achieve an AIDS-free generation – including reaching the UNAIDS 90–90-90 target – thus depends critically on the content of these perceptions. We examined the accuracy of HIV-risk perceptions and their correlates among young black women in South Africa, a group with one of the highest HIV incidence rates worldwide.MethodsWe used individual-level longitudinal data from the Cape Area Panel Study (CAPS) from 2005 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 38 publications
8
54
1
Order By: Relevance
“…Regarding the evidence of validity based on the relationship with other variables, it was observed that the perceived susceptibility to HIV dimension partially explained the SRBs, as noted in previous research [15,39,40,[57][58][59][60]. The observed relationships between perceived susceptibility to HIV and SRBs were in the expected direction (i.e., protective factors), with the exception of the relationship with inappropriate use of protective barriers, which could be attributed to people who tend to not use condoms not perceiving themselves to be at higher risk of HIV infection.…”
Section: Plos Onesupporting
confidence: 63%
“…Regarding the evidence of validity based on the relationship with other variables, it was observed that the perceived susceptibility to HIV dimension partially explained the SRBs, as noted in previous research [15,39,40,[57][58][59][60]. The observed relationships between perceived susceptibility to HIV and SRBs were in the expected direction (i.e., protective factors), with the exception of the relationship with inappropriate use of protective barriers, which could be attributed to people who tend to not use condoms not perceiving themselves to be at higher risk of HIV infection.…”
Section: Plos Onesupporting
confidence: 63%
“…More specifically, we predict that those who are generally more concerned about COVID-19 are more likely to adhere to preventive measures as shown by previous studies, conducted in similar contexts (e.g. Chen, Fox, Cantrell, Stockdale, & Kagawa-Singer, 2007;Lau, Kim, Tsui, & Griffiths, 2007;Maughan-Brown & Venkataramani, 2018). Since it is scientific organizations and scientists who are often the source of both, prevention guidelines and messages informing the public about COVID-19 risks, those who trust science and scientists are more inclined to perceive COVID-19 as an actual risk and follow the risk-mitigating guidelines.…”
Section: Development Of the Modelmentioning
confidence: 72%
“…Among the general population in Nigeria, the HIV stigma level has declined [13], however this is yet to be determined among young adolescents aged 10-14. Similarly on risk perceptions, some studies in Africa [14][15][16] have found perceived low and inaccurate reporting of HIV risks among adolescents. It is therefore beneficial to accurately understand why young adolescents perceive themselves to be at low risk in order to address misconceptions associated with their beliefs.…”
Section: Introductionmentioning
confidence: 99%